The AgroParisTech “Social Openings” mission - Annie Baroiller; Elisabeth Dumoulin (International Journal of Food Studies)
Underprivileged secondary school and college students tend to demonstrate limited ambitions with regards to further education and acquiring superior qualifications. In a partnership with higher education schools, such as AgroParisTech, encounters have been organised between high school students and higher education students acting as volunteering mentors.The aim is to present the high school students with the opportunity to explore new opportunities as well as to provide them with information about high profile careers and higher level training through various activities led by the higher education students, as well as through meetings, visits, weekends organised around a specific theme. Examples of such initiatives  show what benefits both the high school and higher education students can derive from them.